2014
DOI: 10.1016/j.neuron.2014.09.024
|View full text |Cite
|
Sign up to set email alerts
|

PKA-GluA1 Coupling via AKAP5 Controls AMPA Receptor Phosphorylation and Cell-Surface Targeting during Bidirectional Homeostatic Plasticity

Abstract: Summary Bidirectional synaptic plasticity occurs locally at individual synapses during LTP or LTD, or globally during homeostatic scaling. LTP, LTD, and homeostatic scaling alter synaptic strength through changes in post-synaptic AMPARs, suggesting the existence of overlapping molecular mechanisms. Phosphorylation is critical for controlling AMPAR trafficking during LTP/LTD. Here we addressed the role of AMPAR phosphorylation during homeostatic scaling. We observed bidirectional changes of the levels of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
165
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(189 citation statements)
references
References 50 publications
24
165
0
Order By: Relevance
“…As expected, WT neurons exhibited a significant reduction in surface GluA1, GluA2, and GluA3 in response to bicuculline treatment ( Fig. 3 A-D) (9,26). Conversely, TTX-induced inactivity caused a significant increase in surface GluA1 and GluA2 with no change in surface GluA3 (Fig.…”
Section: Inactivity-induced Synaptic Scaling Is Blocked In Grip Knockoutsupporting
confidence: 73%
See 2 more Smart Citations
“…As expected, WT neurons exhibited a significant reduction in surface GluA1, GluA2, and GluA3 in response to bicuculline treatment ( Fig. 3 A-D) (9,26). Conversely, TTX-induced inactivity caused a significant increase in surface GluA1 and GluA2 with no change in surface GluA3 (Fig.…”
Section: Inactivity-induced Synaptic Scaling Is Blocked In Grip Knockoutsupporting
confidence: 73%
“…Several molecules involved in signaling or receptor trafficking are important or required for scaling up, such as AKAP5, PICK1, and Arc (9,11,16), are dispensable for scaling down. Conversely, molecules like Plk2 and PSD-93, though essential for downscaling, are not required for upscaling (15,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TTX reduces calcineurin activity and upregulates phosphorylation of GluA1-S845, and inhibition of calcineurin mimics upscaling in the absence of TTX 139 . Consistent with this, during TTX-induced scaling active PKA is enriched at synapses to mediate phosphorylation of GluA1 S845 and this process also requires the involvement of AKAP150 140 . Together, these data highlight the critical importance of GluA1-S845 phosphorylation in controlling the availability of synaptic CP-AMPARs.…”
Section: Ampar Phosphorylationsupporting
confidence: 64%
“…PKA-mediated phosphorylation of GluA1 S845 has been shown to promote plasma membrane insertion of GluA1 and synaptic retention, thereby facilitating LTP (12,(39)(40)(41)(42)(43), whereas dephosphorylation of S845 by CaN and other phosphatases has been correlated with AMPAR endocytosis and LTD (11,12,40,42). In addition, it has been suggested that regulation of GluA1 S845 phosphorylation by PKA and CaN is involved in AMPAR trafficking during bidirectional homeostatic synaptic plasticity in cortical neurons (44,45; but see ref. 46).…”
Section: Discussionmentioning
confidence: 99%